Increased Prevalence of Subclinical Hypothyroidism and Thyroid Autoimmunity in Depressed Adolescents - Hirtz, Raphael; Focker, Manuel; Libuda, Lars; Antel, Jochen; Ozturk, Dana; Kiewert, Cordula; Munteanu, Martin; Peters, Triinu; Fuhrer, Dagmar; Zwanziger, Denise; Thamm, Michael; Hebebrand, Johannes; et al. (The Journal of Clinical Psychiatry)

Rapid amelioration of anorexia nervosa in a male adolescent during metreleptin treatment including recovery from hypogonadotropic hypogonadism - Antel, Jochen; Tan, Susanne; Grabler, Marvin; Ludwig, Christine; Lohkemper, Dominik; Brandenburg, Tim; Barth, Nikolaus; Hinney, Anke; Libuda, Lars; Remy, Miriam; Milos, Gabriella; Hebebrand, Johannes (European Child & Adolescent Psychiatry)
Abstract With this case report we support our medical hypothesis that metreleptin treatment ameliorates starvation related emotional, cognitive and behavioral symptomatology of anorexia nervosa (AN) and show for the first time strong effects in a male patient with AN. A 15.9 year old adolescent with severe AN of eight-month duration was treated off-label with metreleptin. Hyperactivity was assessed with accelerometry. Visual analogue scales (VAS), validated self- and clinician rating scales and lab results tracked changes from baseline to end of the 24-day dosing period and a five-month follow-up. Substantial improvements of mood and eating disorder related cognitions and hyperactivity set in after two days of treatment. During dosing, sub-physiological testosterone and TT3 levels normalized; clinically libido reemerged. Weight did not increase substantially during the dosing period. During follow-up target weight was attained; mood did not deteriorate; hyperactivity ceased. The results substantiate the strong effects seen in female cases and underscore the need for a double-blind placebo-controlled trial to confirm the observed strong, multiple and rapid onset beneficial effects of metreleptin in AN.

Befähigung zur Reflexion und zum Umgang mit Ambiguitäten. Zur Wirksamkeit von Unterricht für "Lebensführung" - Schlegel-Matthies, Kirsten; Wespi, Claudia (Wirksamer Fachunterricht. Eine metaanalytische Betrachtung von Expertisen aus 17 Schulfächern)

Wirksamer Unterricht für Lebensführung. (Unterrichtsqualität: Perspektiven von Expertinnen und Experten 12) - Schlegel-Matthies, Kirsten; Wespi, Claudia

Wörterbuch. Soziale Arbeit - Klünder, Nina (Wörterbuch. Soziale Arbeit)

Relevance of fructose intake in adolescence for fatty liver indices in young adulthood - Perrar, Ines; Buyken, Anette; Penczynski, Katharina J.; Remer, Thomas; Kuhnle, Gunter G.; Herder, Christian; Roden, Michael; Della Corte, Karen; Nöthlings, Ute; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose To examine the association between fructose intake in adolescence and fatty liver indices (hepatic steatosis index (HSI), fatty liver index (FLI)) in young adulthood. Methods Overall, 246 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had a fasting blood sample in adulthood (18–36 years), at least two 3-day weighed dietary records for calculating fructose intakes and other fructose-containing sugars (total (TS), free (FS), added sugar (AS)) as well as two complete 24-h urine samples for calculating sugar excretion (fructose excretion (FE), fructose + sucrose excretion (FE + SE)) in adolescence (males: 9.5–16.5 years; females: 8.5–15.5 years) were analysed using multivariable linear regression analyses. Results On the level of dietary intake, no prospective associations were observed between adolescent fructose intake and both adult fatty liver indices, whereas higher FS intakes were associated with lower levels of HSI ( P trend = 0.02) and FLI ( P trend = 0.03). On the urinary excretion level, however, a higher FE (P trend = 0.03) and FE + SE ( P trend = 0.01) in adolescence were prospectively related to higher adult FLI values. No associations were observed between adolescent sugar excretion and adult HSI. Conclusion The present study does not provide unambiguous support for a detrimental impact of adolescent fructose intake on adult liver health. Nonetheless, further examinations estimating exposure by means of urinary excretion as well as dietary intake levels appear warranted.

The Prospective Association of Dietary Sugar Intake in Adolescence With Risk Markers of Type 2 Diabetes in Young Adulthood - Della Corte, Karen A.; Penczynski, Katharina; Kuhnle, Gunter; Perrar, Ines; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Remer, Thomas; Alexy, Ute; Buyken, Anette (Frontiers in Nutrition)
Purpose: To examine the prospective relevance of dietary sugar intake (based on dietary data as well as urinary excretion data) in adolescent years for insulin sensitivity and biomarkers of inflammation in young adulthood. Methods: Overall 254 participants of the DONALD study who had at least two 3-day weighed dietary records for calculating intakes of fructose, glucose, sucrose, total, free, added sugars, total sugars from sugar-sweetened beverages (SSB), juice, and sweets/sugar or at least two complete 24 h urine samples ( n = 221) for calculating sugar excretion (urinary fructose and urinary fructose + sucrose) in adolescence (females: 9–15 years, males: 10–16 years) and a fasting blood sample in adulthood (18–36 years), were included in multivariable linear regression analyses assessing their prospective associations with adult homeostasis model assessment insulin sensitivity (HOMA2-%S) and a pro-inflammatory score (based on CRP, IL-6, IL-18, leptin, chemerin, adiponectin). Results: On the dietary intake level, no prospective associations were observed between adolescent fructose, sucrose, glucose, added, free, total sugar, or total sugar from SSB, juice or sweets/sugar intake and adult HOMA2-%S ( p > 0.01). On the urinary level, however, higher excreted fructose levels were associated with improved adult HOMA2-%S ( p = 0.008) among females only. No associations were observed between dietary or urinary sugars and the adult pro-inflammatory score ( p > 0.01). Conclusion: The present study did not provide support that dietary sugar consumed in adolescence is associated with adult insulin sensitivity. The one potential exception was the moderate dietary consumption of fructose, which showed a beneficial association with adult fasting insulin and insulin sensitivity.

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Krüger, Bettina; Nöthlings, Ute; Buyken, Anette E.; Alexy, Ute (European Journal of Clinical Nutrition)
Abstract Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at baseline, 45% females) having at least two measures of chronotype and anthropometry ( N = 572). Chronotype was assessed with the Munich Chronotype Questionnaire and defined as: midpoint of sleep corrected for sleep-debt (MSFsc) accumulated over the week (later MSFsc represents later chronotype). Social jetlag (SJL) defines the difference between midpoint of sleep during week and weekend. Calculations for Fat Free Mass Index (FFMI [kg/m 2 )]) and Fat Mass Index (FMI) [kg/m 2 )]) were based on body fat percentage, weight, and height. To analyze the associations, we used linear mixed-effect regression models. Finally, the total cohort was split into three biologically relevant age groups (cut-off set at <12 years, ≥12 to ≤15 years and >15 years). Results Median follow-up was 2.1 years. Overall, change toward a later chronotype was significantly related with an increase in FMI (ß: 0.05, 95% CI: 0.01–0.08). A 1 h increase in social jetlag predicted an increase in BMI-SDS of 0.08 SDS units (95% CI: 0.01–0.14) and in FMI of 0.04 kg/m2 (95% CI: 0.003–0.08). Associations were stronger for the age group ≥12 to ≤15 years ( p for interaction: <0.001). No relationship was found with FFMI. Conclusions Changes in MSFsc and SJL during adolescence were associated with concurrent changes in BMI-SDS and FMI. The age ≥12 to ≤15 years appears to be a sensitive period in which chronobiological changes were clearly associated with increasing body fatness.

Ebenen der genetischen Analyse komplexer Phänotypen am Beispiel der Anorexia nervosa und der Varianz des Körpergewichts - Hirtz, Raphael; Zheng, Yiran; Rajcsanyi, Luisa S.; Libuda, Lars; Antel, Jochen; Peters, Triinu; Hebebrand, Johannes; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Genetische Varianten beeinflussen die Gewichtsregulation und die Entwicklung von Essstörungen. Zunächst haben familienbasierte, sogenannte formalgenetische Studien den erblichen Anteil an der Gewichtsregulation und an der Ätiologie von Essstörungen beleuchtet. In einer Vielzahl von Studien zeigten sich sowohl für die Varianz des Körpergewichts als auch für die Entstehung von Essstörungen Erblichkeitsschätzer (Heritabilitätsraten) von über 50 %. Mit diesem Wissen begab man sich in den 90er-Jahren des letzten Jahrhunderts auf die Suche nach den zugrundeliegenden Genen (genauer: genetischen Varianten), die das Körpergewicht, das Essverhalten oder beide Phänotypen auf Grundlage geteilter Mechanismen beeinflussen. Zunächst wurden Kandidatengenstudien durchgeführt. Dabei untersuchte man auf Grundlage unterschiedlicher, v. a. aber pathophysiologisch plausibler Überlegungen Gene mit hoher Relevanz für die untersuchten Phänotypen. Dieser Ansatz war für Essstörungen nicht sehr erfolgreich, für die Gewichtsregulation konnte eine Handvoll Gene identifiziert werden. Verbunden mit großen methodischen Fortschritten in der genetischen Forschung und v. a. der Etablierung sogenannter genomweiter Assoziationsstudien (GWAS) Anfang der 2000er-Jahre konnten bislang über 1000 Varianten/Genorte detektiert werden, die das Körpergewicht beeinflussen. Für die Essstörung Anorexia nervosa (AN) sind aktuell acht solcher Genorte beschrieben. Diese Ergebnisse, aber auch aktuelle Ansätze zu phänotypübergreifenden Analysen lassen Einblicke in die komplexe Regulation des Körpergewichtes zu und haben zudem unerwartete Pathomechanismen für AN aufgezeigt.

Ernährungseffekten auf der Spur – Wie die Genetik helfen kann, Zusammenhänge zwischen Ernährung und seelischer Gesundheit aufzudecken - Libuda, Lars; Hebebrand, Johannes; Föcker, Manuel; Peters, Triinu; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Einleitung: Klassische ernährungsepidemiologische Studien (Beobachtungsstudien und randomisierte Interventionsstudien) zeigen, dass die Ernährung ein wichtiger Ansatzpunkt für die Prävention und Therapie psychischer Störungen sein könnte. Diese Studientypen haben allerdings Limitationen, die bei der Ergebnisinterpretation berücksichtigt werden müssen. In dieser narrativen übersichtsarbeit wird beschrieben, wie genetische Studien ein Bindeglied darstellen können, um einen Zusammenhang zwischen Ernährung und psychischen Störungen herzustellen. Methodik: Im Artikel werden verschiedene Ansätze genetischer phänotypübergreifender Analysen sowie Beispiele für deren Anwendungen in der ernährungspsychiatrischen Forschung beschrieben. Darüber hinaus werden spezifische Voraussetzungen sowie Stärken und Schwächen diskutiert. Ergebnisse: Als Methoden genetischer phänotypübergreifender Analysen sind im Rahmen ernährungspsychiatrischer Forschung bislang genetische Korrelationsanalysen, Look-up-Analysen sowie Mendelsche Randomisierungsstudien (MR-Studien) eingesetzt worden. Genetische Korrelationsanalysen und Look-up-Analysen geben erste Hinweise auf mögliche genetische überlappungen zwischen einer psychischen Störung und einem Stoffwechselweg und/oder der Versorgung mit einem spezifischen Nährstoff. MR-Studien sind weitergehende Detailanalysen mit dem Ziel, Kausalzusammenhänge zu identifizieren, beinhalten allerdings sehr spezifische Grundvoraussetzungen für ihre Durchführung. Schlussfolgerung: Genetische phänotypübergreifende Analysen sind eine sinnvolle Ergänzung der klassischen Ernährungsepidemiologie. Insbesondere signifikante Ergebnisse von MR-Studien sind eine wichtige Grundlage zur Entwicklung geeigneter Ernährungsinterventionen, die in nachfolgenden randomisiert kontrollierten Interventionsstudien mit deutlich erhöhter Erfolgsaussicht getestet werden können. Sie sind somit wichtige Instrumente einer effizienten ernährungspsychiatrischen Forschung.

Lack of Evidence for a Relationship Between the Hypothalamus-Pituitary-Adrenal and the Hypothalamus-Pituitary-Thyroid Axis in Adolescent Depression - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Antel, Jochen; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Endocrinology)
In adults with major depressive disorder (MDD), a dysfunction between the hypothalamus-pituitary-adrenal (HPA) and the hypothalamus-pituitary-thyroid (HPT) axis has been shown, but the interaction of both axes has not yet been studied in adolescent major depressive disorder (MDD). Data from 273 adolescents diagnosed with MDD from two single center cross-sectional studies were used for analysis. Serum levels of thyrotropin (TSH), free levothyroxine (fT4), and cortisol were determined as indicators of basal HPT and HPA axis functioning and compared to that of adolescent controls by t-tests. Quantile regression was employed in the sample of adolescents with MDD to investigate the relationship between both axes in the normal as well as the pathological range of cortisol levels, considering confounders of both axes. In adolescent MDD, cortisol levels and TSH levels were significantly elevated in comparison to controls ( p = <.001, d = 1.35, large effect size, and p = <.001, d = 0.79, moderate effect size, respectively). There was a positive linear relationship between TSH and cortisol ( p = .003, d = 0.25, small effect size) at the median of cortisol levels (50 th percentile). However, no relationship between TSH and cortisol was found in hypercortisolemia (cortisol levels at the 97.5 th percentile). These findings imply that HPT and HPA axis dysfunction is common in adolescents with MDD and that function of both axes is only loosely related. Moreover, the regulation of the HPA and HPT axis are likely subjected to age-related maturational adjustments since findings of this study differ from those reported in adults.

Relevance of dietary glycemic index, glycemic load and fiber intake before and during pregnancy for the risk of gestational diabetes mellitus and maternal glucose homeostasis - Zhang, Xiao; Gong, Yunhui; Della Corte, Karen; Yu, Dianke; Xue, Hongmei; Shan, Shufang; Tian, Guo; Liang, Yi; Zhang, Jieyi; He, Fang; Yang, Dagang; Zhou, Rong; et al. (Clinical Nutrition)

Early life factors and their relevance for markers of cardiometabolic risk in early adulthood - Nyasordzi, Juliana; Conrad, Johanna; Goletzke, Janina; Ludwig-Walz, Helena; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Hua, Yifan; Remer, Thomas; Buyken, Anette (Nutrition, Metabolism and Cardiovascular Diseases)

International tables of glycemic index and glycemic load values 2021: a systematic review - Atkinson, Fiona S; Brand-Miller, Jennie C; Foster-Powell, Kaye; Buyken, Anette; Goletzke, Janina (The American Journal of Clinical Nutrition)
ABSTRACT Background Reliable tables of glycemic indexes (GIs) and glycemic loads (GLs) are critical to research examining the relationship between glycemic qualities of carbohydrate in foods, diets, and health. In the 12 years since the last edition of the tables, a large amount of new data has become available. Objectives To systematically review and tabulate published and unpublished sources of reliable GI values, including an assessment of the reliability of the data. Methods This edition of the tables lists over 4000 items, a 61% increase in the number of entries compared to the 2008 edition. The data have been separated into 2 lists. The first represents more precise values derived using the methodology recommended by the International Standards Organization (∼2100 items). The second list contains values determined using less robust methods, including using limited numbers of healthy subjects or with a large SEM (∼1900 food items). Results Dairy products, legumes, pasta, and fruits were usually low-GI foods (≤55 on the 100-point glucose scale) and had consistent values around the world. Cereals and cereal products, however, including whole-grain or whole-meal versions, showed wide variation in GI values, presumably arising from variations in manufacturing methods. Breads, breakfast cereals, rice, savory snack products, and regional foods were available in high-, medium-, and low-GI versions. Most varieties of potato were high-GI foods, but specific low-GI varieties have now been identified. Conclusions The availability of new data on the GIs of foods will facilitate wider research and application of the twin concepts of GI and GL. Although the 2021 edition of the tables improves the quality and quantity of GI data available for research and clinical practice, GI testing of regional foods remains a priority. This systematic review was registered in PROSPERO as #171204.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Anterior cruciate ligament injury mechanisms through a neurocognition lens: implications for injury screening - Gokeler, Alli; Benjaminse, Anne; Della Villa, Francesco; Tosarelli, Fillippo; Verhagen, Evert; Baumeister, Jochen (BMJ Open Sport & Exercise Medicine)
Athletes in team sports have to quickly visually perceive actions of opponents and teammates while executing their own movements. These continuous actions are performed under time pressure and may contribute to a non-contact ACL injury. However, ACL injury screening and prevention programmes are primarily based on standardised movements in a predictable environment. The sports environment provides much greater cognitive demand because athletes must attend their attention to numerous external stimuli and inhibit impulsive actions. Any deficit or delay in attentional processing may contribute to an inability to correct potential errors in complex coordination, resulting in knee positions that increase the ACL injury risk. In this viewpoint, we advocate that ACL injury screening should include the sports specific neurocognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Rehabilitation strategies of Flemish physical therapists before and after anterior cruciate ligament reconstruction: An online survey - Dingenen, Bart; Billiet, Bart; De Baets, Liesbet; Bellemans, Johan; Truijen, Jan; Gokeler, Alli (Physical Therapy in Sport)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - Sherman, David A.; Lehmann, Tim; Baumeister, Jochen; Grooms, Dustin R.; Norte, Grant E. (Experimental Brain Research)
Keywords: General Neuroscience

Effective Attentional Focus Strategies after Anterior Cruciate Ligament Reconstruction: A Commentary - Singh, Harjiv; Gokeler, Alli; Benjaminse, Anne (International Journal of Sports Physical Therapy)
Keywords: General Earth and Planetary Sciences; General Environmental Science

An Exploratory Meta-Analytic Review on the Empirical Evidence of Differential Learning as an Enhanced Motor Learning Method - Tassignon, Bruno; Verschueren, Jo; Baeyens, Jean-Pierre; Benjaminse, Anne; Gokeler, Alli; Serrien, Ben; Clijsen, Ron (Frontiers in Psychology)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory, and to date, no overview exists that compares the effects of DL to other motor learning methods. Objective: To evaluate the effectiveness of DL in comparison to other motor learning methods in the acquisition and retention phase. Design: Systematic review and exploratory meta-analysis. Methods: PubMed (MEDLINE), Web of Science, and Google Scholar were searched until February 3, 2020. To be included, (1) studies had to be experiments where the DL group was compared to a control group engaged in a different motor learning method (lack of practice was not eligible), (2) studies had to describe the effects on one or more measures of performance in a skill or movement task, and (3) the study report had to be published as a full paper in a journal or as a book chapter. Results: Twenty-seven studies encompassing 31 experiments were included. Overall heterogeneity for the acquisition phase (post-pre; I 2 = 77%) as well as for the retention phase (retention-pre; I 2 = 79%) was large, and risk of bias was high. The meta-analysis showed an overall small effect size of 0.26 [0.10, 0.42] in the acquisition phase for participants in the DL group compared to other motor learning methods. In the retention phase, an overall medium effect size of 0.61 [0.30, 0.91] was observed for participants in the DL group compared to other motor learning methods. Discussion/Conclusion: Given the large amount of heterogeneity, limited number of studies, low sample sizes, low statistical power, possible publication bias, and high risk of bias in general, inferences about the effectiveness of DL would be premature. Even though DL shows potential to result in greater average improvements between pre- and post/retention test compared to non-variability-based motor learning methods, more high-quality research is needed before issuing such a statement. For robust comparisons on the relative effectiveness of DL to different variability-based motor learning methods, scarce and inconclusive evidence was found.
Keywords: General Psychology

High Incidence of Anterior Cruciate Ligament Injuries Within the First 2 Months of the Season in Amateur Team Ball Sports - Mouton, Caroline; Gokeler, Alli; Urhausen, Anouk; Nührenbörger, Christian; Seil, Romain (Sports Health: A Multidisciplinary Approach)
Background: The incidence of anterior cruciate ligament (ACL) injuries is commonly reported as an annual incidence rate. There is relatively little information about the seasonal aspects of these injuries. The aim of the current study was to analyze the distribution of ACL injuries during the season in nonprofessional soccer, handball, and basketball based on a retrospective analysis of a hospital-based registry. Hypothesis: ACL injuries in soccer, handball, and basketball were more common within the first 2 months of the season in comparison with the rest of the year. Study Design: Case series. Level of Evidence: Level 4. Methods: Injury occurrence during the calendar year was divided into 6 periods of 2 months, with segment 1 (S1) representing the first 2 months of the season. For soccer, S1 corresponded to September and October. The season started 1 month later for handball and basketball, so S1 represented October and November. Chi-square tests were used to analyze the distribution of ACL injuries among segments according to gender, age, sports, and injury mechanism (contact/noncontact). Results: A total of 371 ACL injuries were included (soccer, 258, handball, 56, basketball, 57). Overall, the distribution of ACL injuries was not uniform across the segments ( P < 0.01). Almost one-third of the ACL injuries occurred in S1 (n = 104; 28%). Significant differences could be observed according to sports ( P < 0.01). There were fewer ACL injuries in S2 for soccer compared with basketball ( P < 0.05). In S5, there were significantly more ACL injuries in soccer compared with handball and basketball ( P < 0.05). Conclusion: A high occurrence of ACL injuries was reported immediately within the first 2 months of the season in nonprofessional soccer, handball, and basketball sports. Clinical Relevance: These findings indicate that ACL injury prevention programs should be started in the preseason period to allow for gradual increases of load.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The modifying factors that help improve anterior cruciate ligament reconstruction rehabilitation: A narrative review - Rambaud, Alexandre JM; Neri, Thomas; Dingenen, Bart; Parker, David; Servien, Elvire; Gokeler, Alli; Edouard, Pascal (Annals of Physical and Rehabilitation Medicine)
Keywords: Rehabilitation; Orthopedics and Sports Medicine

An ecological dynamics approach to ACL injury risk research: a current opinion - Bolt, Ruben; Heuvelmans, Pieter; Benjaminse, Anne; Robinson, Mark A.; Gokeler, Alli (Sports Biomechanics)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

Maternal pregnancy weight or gestational weight gain and offspring's blood pressure: A systematic review - Ludwig-Walz, Helena; Nyasordzi, Juliana; Weber, Katharina S.; Buyken, Anette; Kroke, Anja (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Size Matters: The CAG Repeat Length of the Androgen Receptor Gene, Testosterone, and Male Adolescent Depression Severity - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Psychiatry)
There is a distinct increase in the prevalence of depression with the onset of puberty. The role of peripubertal testosterone levels in boys in this context is insufficiently understood and may be modulated by a functional polymorphism of the androgen receptor gene (AR), a variable number of CAG repeats. Moreover, there is preliminary evidence that the relationship between testosterone, CAG repeat length, and the severity of depressive symptoms may differ between subclinical and overt depression, but this has neither been studied in a clinical sample of adolescents with depression nor compared between subclinical and overt depression in an adequately powered study. To investigate the relationship between free testosterone, CAG repeat length of the AR, depression status (subclinical vs. overt), and the severity of depressive symptoms, 118 boys treated as in- or daycare patients at a single psychiatric hospital were studied. Of these, 73 boys had at least mild depressive symptoms according to the Beck Depression Inventory-II (BDI-II > 13). Higher-order moderation analysis in the multiple regression framework revealed a constant relationship between free testosterone and depression severity irrespective of the number of CAG repeats in adolescents with a BDI-II score ≤ 13. In adolescents with a BDI-II score > 13, however, there was a significant negative relationship between free testosterone and BDI-II score in patients with <19 CAG repeats and a significant positive relationship regarding free testosterone and BDI-II score in those with more than 28 CAG repeats, even when considering important covariates. These results suggest that the effects of testosterone on mood in male adolescents with depression depend on the genetic make-up of the AR as well as on depression status. This complex relationship should be considered by future studies addressing mental health issues against an endocrine background and may, moreover, contribute to tailored treatment concepts in psychiatric medicine, especially in adults.

Vitamin D Level Trajectories of Adolescent Patients with Anorexia Nervosa at Inpatient Admission, during Treatment, and at One Year Follow Up: Association with Depressive Symptoms - Föcker, Manuel; Timmesfeld, Nina; Bühlmeier, Judith; Zwanziger, Denise; Führer, Dagmar; Grasemann, Corinna; Ehrlich, Stefan; Egberts, Karin; Fleischhaker, Christian; Wewetzer, Christoph; Wessing, Ida; Seitz, Jochen; et al. (Nutrients)
(1) Background: Evidence has accumulated that patients with anorexia nervosa (AN) are at higher risk for vitamin D deficiency than healthy controls. In epidemiologic studies, low 25(OH) vitamin D (25(OH)D) levels were associated with depression. This study analyzed the relationship between 25(OH)D serum levels in adolescent patients and AN and depressive symptoms over the course of treatment. (2) Methods: 25(OH)D levels and depressive symptoms were analyzed in 93 adolescent (in-)patients with AN from the Anorexia Nervosa Day patient versus Inpatient (ANDI) multicenter trial at clinic admission, discharge, and 1 year follow up. Mixed regression models were used to analyze the relationship between 25(OH)D levels and depressive symptoms assessed by the Beck Depression Inventory (BDI-II). (3) Results: Although mean 25(OH)D levels constantly remained in recommended ranges (≥50 nmol/L) during AN treatment, levels decreased from (in)patient admission to 1 year follow up. Levels of 25(OH)D were neither cross-sectionally, prospectively, nor longitudinally associated with the BDI-II score. (4) Conclusions: This study did not confirm that 25(OH)D levels are associated with depressive symptoms in patients with AN. However, increasing risks of vitamin D deficiency over the course of AN treatment indicate that clinicians should monitor 25(OH)D levels.

Alterations in B cell subsets correlate with body composition parameters in female adolescents with anorexia nervosa - Freff, Jana; Schwarte, Kathrin; Bröker, Lisa; Bühlmeier, Judith; Kraft, Isabelle; Öztürk, Dana; Hinney, Anke; Arolt, Volker; Dannlowski, Udo; Romer, Georg; Baune, Bernhard T.; Hebebrand, Johannes; et al. (Scientific Reports)
Abstract Anorexia nervosa (AN) is a severe eating disorder and often associated with altered humoral immune responses. However, distinct B cell maturation stages in peripheral blood in adolescents with AN have not been characterized. Treatment effects and the relationship between clinical and B cell parameters are also not fully understood. Here we investigated the phenotype of circulating B cell subsets and the relationship with body composition in adolescents with AN before (T0, n = 24) and after 6 weeks (T1, n = 20) of treatment. Using multi-parameter flow cytometry, we found increased percentages of antigen-experienced B cells and plasmablasts in patients with AN compared to healthy controls (n = 20). In contrast, percentages of CD1d + CD5 + B cells and transitional B cells with immunoregulatory roles were reduced at T0 and T1. These B cell frequencies correlated positively with fat mass, fat mass index (FMI), free fat mass index, and body mass index standard deviation score. In addition, scavenger-like receptor CD5 expression levels were downregulated on transitional B cells and correlated with fat mass and FMI in AN. Our findings that regulatory B cell subgroups were reduced in AN and their strong relationship with body composition parameters point toward an impact of immunoregulatory B cells in the pathogenesis of AN.

Kurzzeitige Behandlung von Patient_innen mit Anorexia nervosa mit rekombinant hergestelltem Human-Leptin (Metreleptin): Rasch einsetzende positive Effekte auf Stimmung, Kognition und Verhalten - Hebebrand, Johannes; Antel, Jochen; Tan, Susanne; Wabitsch, Martin; Wiesing, Urban; Barth, Nikolaus; Ludwig, Christine; Bühlmeier, Judith; Libuda, Lars; Milos, Gabriella; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)

Impact of lunch with carbohydrates differing in glycemic index on children's cognitive functioning in the late postprandial phase: a randomized crossover study - Drozdowska, Alina; Sinningen, Kathrin; Falkenstein, Michael; Rudolf, Henrik; Libuda, Lars; Buyken, Anette; Lücke, Thomas; Kersting, Mathilde (European Journal of Nutrition)
Abstract Purpose Studies about effects of lunch dietary Glycemic Index (GI) on cognition of schoolchildren are scarce. Our previous CogniDo GI study found no changes of cognition in the early postprandial phase after consumption of two rice types with medium vs. high dietary GI for lunch (i.e., 45 min after starting lunch). This study investigated whether the dietary GI of lunch has an impact on cognition of schoolchildren in the late postprandial phase, 90 min after lunch. Methods A randomized, 2 × 2 crossover intervention study was conducted at a comprehensive school with 5th and 6th grade students. Participants ( n = 212) were randomly assigned to either sequence 1 or 2. In the first period, participants of sequence 1 received a dish with high GI rice (GI: 79), those of sequence 2 with medium GI rice (GI: 64)—in the second period, 1 week later, vice versa. Computer-based cognitive testing was performed 90 min after lunch examining tonic alertness, visual search and task switching, and working memory. Treatment effects and treatment effects adjusted for estimated lunch glycemic load (GL) were analyzed using a linear mixed model. Results The selected cognitive parameters were not affected by the GI of lunch 90 min after lunch, neither after intention-to-treat nor in the per-protocol analysis. Adjustment for GL also did not change results. Conclusion The present study revealed no notable differences after the consumption of two rice types with medium vs. high dietary GI for lunch in children’s cognitive function in the late postprandial phase, 90 min after lunch. Clinical trial registration German Clinical Trials Register (DRKS00013597); date of registration: 16/04/2018, retrospectively registered.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Mentale Rotationsleistungen bei der Betrachtung und Umsetzung von Spielzügen im Basketball: Novizen vs. erfahrene Basketballspieler - Krause, Daniel; Behrens, J.B.; Löhers, L.; Weigelt, Matthias

Representations after mentally practiced one finger sequences are effector independent - Dahm, Stephan; Weigelt, Matthias; Rieger, M.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, J.A.; Figueiredo, G.A.; Weigelt, Matthias

How does spectator presence affect football? Home advantage remains in European top-class football matches played without spectators during the COVID-19 pandemic - Wunderlich, Fabian; Weigelt, Matthias; Rein, Robert; Memmert, Daniel (PLOS ONE)
The present paper investigates factors contributing to the home advantage, by using the exceptional opportunity to study professional football matches played in the absence of spectators due to the COVID-19 pandemic in 2020. More than 40,000 matches before and during the pandemic, including more than 1,000 professional matches without spectators across the main European football leagues, have been analyzed. Results support the notion of a crowd-induced referee bias as the increased sanctioning of away teams disappears in the absence of spectators with regard to fouls (p < .001), yellow cards (p < .001), and red cards (p < .05). Moreover, the match dominance of home teams decreases significantly as indicated by shots (p < .001) and shots on target (p < .01). In terms of the home advantage itself, surprisingly, only a non-significant decrease is found. While the present paper supports prior research with regard to a crowd-induced referee bias, spectators thus do not seem to be the main driving factor of the home advantage. Results from amateur football, being naturally played in absence of a crowd, provide further evidence that the home advantage is predominantly caused by factors not directly or indirectly attributable to a noteworthy number of spectators.
Keywords: Multidisciplinary

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.
Keywords: General Engineering

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Keywords: General Neuroscience

An interrater reliability study of gait analysis systems with the dual task paradigm in healthy young and older adults - Klotzbier, Thomas Jürgen; Wollesen, Bettina; Vogel, Oliver; Rudisch, Julian; Cordes, Thomas; Jöllenbeck, Thomas; Vogt, Lutz (European Review of Aging and Physical Activity)
Abstract Background and aims One reason for the controversial discussion of whether the dual task (DT) walking paradigm has an added value for diagnosis in clinical conditions might be the use of different gait measurement systems. Therefore, the purpose was 1) to detect DT effects of central gait parameters obtained from five different gait analysis devices in young and old adults, 2) to assess the consistency of the measurement systems, and 3) to determine if the absolut and proportional DT costs (DTC) are greater than the system-measurement error under ST. Methods Twelve old (72.2 ± 7.9y) and 14 young adults (28.3 ± 6.2y) walked a 14.7-m distance under ST and DT at a self-selected gait velocity. Interrater reliability, precision of the measurement and sensitivity to change were calculated under ST and DT. Results An age effect was observed in almost all gait parameters for the ST condition. For DT only differences for stride length ( p < .029, ɳ 2 p = .239) as well as single and double limb support ( p = .036, ɳ 2 p = .227; p = .034, ɳ 2 p = .218) remained. The measurement systems showed a lower absolute agreement compared to consistency across all systems. Conclusions When reporting DT effects, the real changes in performance and random measurement errors should always be accounted for. These findings have strong implications for interpreting DT effects.
Keywords: Geriatrics and Gerontology

Agreement and consistency of five different clinical gait analysis systems in the assessment of spatiotemporal gait parameters - Rudisch, Julian; Jöllenbeck, Thomas; Vogt, Lutz; Cordes, Thomas; Klotzbier, Thomas Jürgen; Vogel, Oliver; Wollesen, Bettina (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)

Head injuries in professional football (soccer): Results of video analysis verified by an accident insurance registry. - Krutsch, V; Krutsch, W; Härtl, J; Bloch, H; Alt, V; Klein, C; Reinsberger, Claus; Seiffert, R; Huber, L; Weber, J (PLoS One)

Evaluation of Open-Source and Pre-Trained Deep Convolutional Neural Networks Suitable for Player Detection and Motion Analysis in Squash. - Brumann, C; Kukuk, M; Reinsberger, Claus (Sensors (Basel))

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning